The Crisis of Social Institutions and Police Homicides: The Adverse Effects of Low Institutional Control - Wetherell, Kamali’ilani T. E. (Homicide studies, 2022)
Using U.S. census data and a multi-source database on officer-involved killings, the current study extends previous research by exploring the influence of measures of weak social control in economic, educational, and familial institutions on state rates of police homicide. States with lower levels of institutional control are found to have higher overall rates of police homicides and police killings involving Black, Hispanic, and White decedents. The significant effects of institutional control on these police homicide rates are generally found to exhibit contextual invariance across different levels of various control variables (e.g., comparisons of states with low or high violent crime rates, low vs high economic inequality, low vs high levels of urbanization). These results and the limitations of this study are discussed in terms of implications for future research and public policy on police homicides and the role of social institutions in minimizing the occurrence of these incidents.